Smart Farm - Ahmad Ratrout; Mohammad Doudar (My University, 2022)
Technology has been used in almost every field in our life, Which makes our life much easier. The project aims to eliminate the repetitive process of farming and make the farmer’s life easier and save time which can be spent on more important things. Smart Farm will measure the humidity of the soil and will water the plants based on the soils need using a grid system which means that the pump will move to the cell that has a low humidity in the soil and water the plant till the moister in the soil to have the right amount, as well as there is a light that well turn on based on how much light detected so that the plants will get light even in the nights, and we have a fan that is controlled by the temperature sensor so if the temperature is larger than the cutoff value the fan will work, there is also android application that is used to configure cutoff value and more as well as the fan can be replaced with a heater for a colder weathers, so also in the application the operation can be replaced so that a heater can be used instead of the larger than it can be configured to be smaller than. the project have used arduino uno as well as an esp8266 NodeMCU, and it have a humidity sensor, temperature sensor as well as a moister sensor for the soil, and the esp8266 have a web server with RESTful endpoints for creating a clients for it. iv